PENGEMBANGAN BAHAN AJAR BERBASIS FLIPBOOK DIGITAL PADA PEMBELAJARAN IPAS KELAS V SD - Latifa Aurumi; Adrianus Dedy; Erfan Ramadhani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the lack of variety of teaching materials and the limited use of technology in the learning process, so that the learning process becomes less active and less interesting for students. To overcome this, researchers developed digital flipbook-based teaching materials in grade V IPAS learning with the material “My Indonesia is Rich in Biology”. The purpose of this study was to produce teaching materials that are valid, practical and effective. This research and development uses the ADDIE development model which consists of 5 (five) stages: Analyze, Design, Development, Implementation, and Evaluation. Data analysis was conducted to assess the validity, practicality, and effectiveness of teaching materials. The results showed that the developed digital flipbook-based teaching materials had a “High” level of validity with an average Aiken's V value of 0.84. The level of practicality of teaching materials is in the “Very Practical” category with an average value of 91.77%. The effectiveness of this teaching material is also “High” with an average N-Gain score of 0.91. Thus, it can be concluded that digital flipbook-based teaching materials in grade V IPAS learning are categorized as valid, practical, and effective and are suitable for use in the IPAS learning process.